1995
DOI: 10.1021/bi00022a007
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Arginine-11 in the N-Terminal Helix of Skeletal Troponin C: Combined Mutagenesis and Molecular Dynamics Investigation

Abstract: The two main structural differences between calmodulin (CaM) and skeletal troponin C (sTnC) are the absence in CaM of (i) the short N-terminal helix in TnC and (ii) the triplet KGK (residues 91-93; numbering according to chicken sTnC). It was recently shown that deletion of both structural groups from sTnC imparted to the resulting construct the CaM-like ability to activate phosphodiesterase (PDE) and to regulate force development in smooth muscle. To continue probing of the structural basis of the differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
(82 reference statements)
1
2
1
Order By: Relevance
“…Loss of Arg11 or the N helix in general would destabilize loop II and cause the observed decrease in calcium af®nity and calcium-regulated activity. Our observation disputes earlier molecular dynamic simulations on a modelled 4-Ca 2 -TnC, which suggested that upon calcium uptake, Arg11 and Glu76 would signi®cantly break apart such that their interaction was via a network of water molecules rather than via a direct ion pair (Gulati et al, 1995).…”
Section: The N Helixcontrasting
confidence: 99%
“…Loss of Arg11 or the N helix in general would destabilize loop II and cause the observed decrease in calcium af®nity and calcium-regulated activity. Our observation disputes earlier molecular dynamic simulations on a modelled 4-Ca 2 -TnC, which suggested that upon calcium uptake, Arg11 and Glu76 would signi®cantly break apart such that their interaction was via a network of water molecules rather than via a direct ion pair (Gulati et al, 1995).…”
Section: The N Helixcontrasting
confidence: 99%
“…The prediction that the loss of Arg 11 (or the salt bridge) would destabilize loop 2 and decrease Ca 2ϩ affinity was not borne out by our assays, although deletion of the entire N-helix does reduce the Ca 2ϩ affinity of the N-domain (Chandra et al, 1994;Smith et al, 1994). Our results are in agreement with Gulati et al (1995) who reported that an R11A mutant could restore full tension regulation in TnC-depleted fibers.…”
Section: Effect Of Destroying the Arg 11-glu 76 Salt Bridgesupporting
confidence: 94%
“…Most often, the difficulty of escaping from the close vicinity of a starting conformation was found to be formidable. Broader sampling of the conformational space could be achieved if the covalent or intradomain structure of a protein was preserved by a series of restraints, [26][27][28] and/or atomic masses were artificially increased. 29 Among other methods that may be applicable to large-scale domain rearrangement modeling, are random and friction forces molecular dynamics, 30 internal coordinate molecular dynamics, [31][32][33][34] stochastic rigid body, and brownian dynamics with simplified residue representation, [35][36] Monte Carlo calculations in space of scaled collective internal variables, 37 and ''essential dynamics.''…”
Section: Introductionmentioning
confidence: 99%